Innovation and development product based on the salt potential of Madura: Fortified Moringa Salt - Iffan Maflahah; Dian Farida Asfan (President University, 2022)
This study aims to identify the development process of fortified moringa salt based on Madura Island's potential. Analytical Hierarchy Process (AHP) methods used the commercialization strategy scenarios. SWOT analysis was used to select alternative strategies formulated. The results are moringa fortified salt product contains 87% NaCl, 11.88 µg/g vitamin C, 4.88 µg/g B-carotene, 3.6% water content, and 46.713 ppm antioxidant content so that it meets the requirements as health salt; the development of salt products is carried out by making a new product in moringa fortified salt for the upper-middle class and hypertension. The priority of the product commercialization strategy that is carried out is to open a new business, a joint system between farmers and business people or other related parties, and a drop selling system to increase salt farmers' revenue.